The Role of Counselors in Handling Traumatic Victims of Sexual Violence - Maynawati, Aldila Fitri Radite Nur; saputro, Billdy; Setyawan, Akhmad; Rahmawati, Sinta Nalita Sari (Cognitive Development Journal, 2024)
Sexual violence is a case of violence that still occurs in Indonesia, even Sukoharjo Regency. This phenomenon is of particular concern to government agencies, namely DPPKBP3A Sukoharjo Regency. This government institution has a counselor who is required to be able to meet the current needs of society. Namely in the process of assisting victims of sexual violence. This is because sexual violence that occurs on children will have a negative impact. Children who experience sexual violence will be psychologically disturbed and can disrupt their growth and development process. The role of the counselor here is very important, not only in psychological assistance but also in his role during the counseling process and carrying out the functions of a counselor. The focus of this research is the role of counselors in dealing with traumatic victims of sexual violence. The conclusion of this research is that the role of counselors is very important in treating traumatic victims of sexual violence. The programs provided by DPPKBP3A Sukoharjo Regency are very helpful in treating victims of sexual violence. Inhibiting factors and clouding factors are obstacles and opportunities in assisting the treatment of victims of sexual violence.